Supervision Function of the Environmental Service in Overcoming Environmental Pollution in the City of Makassar - Purna, Zarni Adia; Guntur, Muhammad; Putri, Andini Eka; Johansyah, Oky Nur Pratiwi (Universitas Negeri Makassar, 2024)
This study aims to determine the supervisory function of the environmental service in handling environmental pollution in the city of Makassar. The type of research used in this study is descriptive qualitative, namely problem-solving procedure investigate by observing a current state of the object of research based on visible fact or as they are. The result of this study indicate that the Makassar City Environmental Service has the main tasks of formulate, foster, coordinate and controling policies in the environment sector including environment impact analysis, environment impact recovery and compliance with environmental law. Besides that, the Supervision Function of the Environmental Service in Handling Environmental Pollution in Makassar City. The Department of the Environment has not maximized in supervising the management of Domestic waste, especially plastic waste with consideration of factors, including the lack of understanding by the industry regarding plastic waste. The government's supervision strategy in the management of domestic waste, especially plastic waste, requires continuity between the government, industrial entrepreneurs and NGOs to achieve the objectives of good supervision and management of domestic waste, especially plastic waste.